2019
DOI: 10.1021/acs.analchem.9b01293
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of Mitochondrial Viscosity in Inflammation, Fatty Liver, and Cancer Living Mice by a Robust Fluorescent Probe

Abstract: Elucidating the internal relationship between diseases and mitochondrial viscosity remains a great challenge due to the lack of the studies on multidisease living animals. So far, demonstrating abnormal mitochondria viscosity in the fatty liver and tumor living mice has not been achieved. To address this critical challenge, the powerful two-photon and mitochondria-targeted fluorescence probe CBI-V was designed herein for viscosity detection with deep red emission. Utilizing the new probe CBI-V, the mitochondri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
70
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(79 citation statements)
references
References 50 publications
4
70
0
Order By: Relevance
“…Further fluorescence imaging and fluorescence lifetime imaging (FLIM) utilizing probe 3 illustrated that lipopolysaccharide (LPS) treated cells possessed clearly enhanced viscosity in mitochondria. Probe 4 , as a hybrid of carbazole and indole salt moiety, was employed to visualize mitochondrial viscosity in inflamed tissue, fatty liver, as well as cancer tissue [31] . The imaging results demonstrated that all these pathosises were accompanying by an increase of viscosity.…”
Section: Small Molecular Fluorescent Probes For Viscositymentioning
confidence: 99%
“…Further fluorescence imaging and fluorescence lifetime imaging (FLIM) utilizing probe 3 illustrated that lipopolysaccharide (LPS) treated cells possessed clearly enhanced viscosity in mitochondria. Probe 4 , as a hybrid of carbazole and indole salt moiety, was employed to visualize mitochondrial viscosity in inflamed tissue, fatty liver, as well as cancer tissue [31] . The imaging results demonstrated that all these pathosises were accompanying by an increase of viscosity.…”
Section: Small Molecular Fluorescent Probes For Viscositymentioning
confidence: 99%
“…In addition, the reduction of the omega-6/omega-3 balance and the omega-3 incorporation into mitochondrial membranes increase its viscosity. This situation improves mitochondrial function and avoids cell dysfunction and cell death [ 137 ]. However, the disbalanced omega-3/omega-6 ratio in detriment of omega-6 may also lead to adverse consequences, since excessive omega-3 PUFAs may eventually trigger pro-oxidant and pro-inflammatory environments [ 138 ].…”
Section: Nutrients (Well-being Through Feeding)mentioning
confidence: 99%
“…Having verified the ability of TTPB to separately image mitochondrial viscosity and H 2 O 2 in two different channels, we then evaluate its capability of simultaneously tracking mitochondrial viscosity and H 2 O 2 in an inflammation model induced by lipopolysaccharide (LPS), which has been verified to trigger cells to produce inflammation. [ 33‐34 ]…”
Section: Resultsmentioning
confidence: 99%